2013
DOI: 10.1186/2050-5736-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Safety and treatment volumes achieved following new developments of the magnetic resonance-guided focused ultrasound system in the treatment of uterine fibroids: a cohort study

Abstract: BackgroundThis research investigates whether modifications to the magnetic resonance-guided focused ultrasound ablation of uterine fibroid (MRgFUS) system used resulted in improved treatment volumes of uterine fibroids, while maintaining safety.MethodsThis study is a prospective cohort analysis of 34 women undergoing the ExAblate 2100 MRgFUS treatment for their uterine fibroids.ResultsThe percentage of non-perfused volume (NPV) achieved with the ExAblate 2100 system was 54.92% compared with 50.49 % with the Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Post treatment predictor of success is the non-perfused volume of the leiomyoma. Treatment typically achieves around 50–55% non-perfused volume, based on post contrast imaging after the completion of treatment [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post treatment predictor of success is the non-perfused volume of the leiomyoma. Treatment typically achieves around 50–55% non-perfused volume, based on post contrast imaging after the completion of treatment [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the ExAblate 2100 system has increased the NPVs achieved in fibroids, in particular in those fibroids of higher signal intensity [20]. A study by Trumm et al found mean NPV ratios of 88 AE 15% (range 38-100%) using the new ExAblate 2100 system [21].…”
Section: Ethnicitymentioning
confidence: 97%
“…Independent control of element phase and amplitude is important for active tissue aberration correction. First, phase control allows the electronic steering of the focus, which can enlarge the treated volume and increase treatment efficiency 30,31 . Second, the ability to deactivate specific transducer elements allows the user to avoid sonicating through normal tissues or organs at risk, such as the ribs, nerves or bowel 32 …”
Section: Components Of a Clinical Body Mrgfus Systemmentioning
confidence: 99%
“…First, phase control allows the electronic steering of the focus, which can enlarge the treated volume and increase treatment efficiency. 30,31 Second, the ability to deactivate specific transducer elements allows the user to avoid sonicating through normal tissues or organs at risk, such as the ribs, nerves or bowel. 32 The drive electronics are sited with the MR electronics and fed through filtered penetration panels into the treatment room.…”
Section: Transducer Drive Electronicsmentioning
confidence: 99%